Primary Extraskeletal Ewing Sarcoma of the Thoracolumbar Epidural Space: Rare Case Report in a Child - Silva, Aldo José Ferreira da; Ruela Pires, Ana Carolina de Carvalho; Costa, Auxiliadora Damianne Pereira Vieira da; Amaral, Fabiana Lopes; Bomfim, Rodrigo C.; Bomfim Filho, Ângelo M. S.; Feitosa, Alessandra Lamenha; Buarque, Igor Lima (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Ewing sarcomas are a family of tumors that can be of skeletal or extraskeletal origin. We report a rare case of a child with extraskeletal Ewing sarcoma in the thoracolumbar epidural space.Case Report The patient was a 1-year-old female child with sphincter alteration, flaccid paraplegia, and areflexia. A magnetic resonance imaging (MRI) scan showed a large extensive epidural lesion with compression of the dural sac in the D6–L2 segment, and a left paravertebral extension through the L1–L2 foramen. Laminotomy was performed, with subtotal resection of the lesion. The histopathological and immunohistochemical analyses indicated Ewing sarcoma. Due to the child's age, radiotherapy was not performed, only chemotherapy, due to the aggressiveness of the neoplasm. The patient showed rapid tumor recurrence and ended up dying.Discussion Extraskeletal Ewing sarcoma can appear in different locations in the body. They are aggressive tumors with local recurrence and distant metastases. In our case, a combination of MRI and positron-emission tomography–computed tomography scan presented a clearer result, especially in the presence of metastasis. In the histopathological analysis, small blue cells with a clear cytoplasm and indistinct nucleoli were observed. In the immunohistochemical analysis, CD99 (MIC2) expression is highlighted. The best treatment outcome would have been surgical resection with chemotherapy and radiotherapy.Conclusion We reported a rare case of thoracolumbar epidural Ewing sarcoma in which, despite surgery and chemotherapy, the tumor behaved very aggressively, leading to an unfavorable prognosis.
Keywords: Ewing sarcoma; thoracolumbar; epidural; radiotherapy; chemotherapy